Adherence to Physical Activity and Incident Mobility Disability in Older Adults With Mobility Limitations - Álvarez-Bustos, Alejandro; Coelho-Junior, Helio José; Calvani, Riccardo; Rodriguez-Mañas, Leocadio; Tosato, Matteo; Cesari, Matteo; Cherubini, Antonio; Cruz-Jentoft, Alfonso J; Jónsson, Pálmi V; Lattanzio, Fabrizia; Maggio, Marcello; Roller-Wirnsberger, Regina; et al. (Journal of cachexia, sarcopenia and muscle, 2025)
BACKGROUND: Preservation of mobility independence is a primary goal in older adults with physical frailty and sarcopenia (PF&S). Interventions based on the combination of physical activity (PA) and nutritional counselling have been indicated as strategies for the management of this condition, although their effectiveness is not confirmed in all investigations. A possible explanation for this uncertain scenario relies in the impact of the adherence to PA interventions. Hence, the present study investigated the impact of the adherence to PA sessions on the incidence of mobility disability in older adults with PF&S. METHODS: This is a secondary analysis of an evaluator blinded, randomised controlled trial, developed in 16 clinical sites across 11 European countries, from January 2016 to 31 October 2019. Participants were community-dwelling older adults (70+ years) with PF&S enrolled in the SPRINTT trial (NCT02582138). PF&S was operationalised as having a total score from 3 to 9 on the short physical performance battery (SPPB), low appendicular lean mass and ability to complete the 400-m walk test in < 15 min. Data from participants allocated to a multicomponent intervention (PA with technological support plus nutritional counselling) and a healthy ageing lifestyle education programme (control group) were analysed. Adherence to PA was assessed based on the number of weekly sessions attended. According to recommendations of the American College of Sports Medicine, adherence was categorised as below recommendations (< 2 sessions/week, BR), meeting recommendations (2-3 sessions/week, MR), and above recommendations (> 3 sessions/week, AR). The primary outcome was incident mobility disability, operationalised as incident inability to complete the 400-m walk test in < 15 min during up to 36 months of follow-up. RESULTS: Data of 1444 participants (mean age 79.3 years, 72.6% women) were analysed. In those with SPPB scores of 3-7, MR and AR groups had lower risk of mobility disability compared with controls [MR HR (95% CI): 0.57 (0.41-0.78), p = 0.001; AR HR (95% CI): 0.33 (0.23-0.46), p < 0.001] and BR groups [MR: HR (95% CI): 0.48 (0.34-0.69), p < 0.001; AR: HR (95% CI): 0.27 (0.18-0.38), p < 0.001] in a dose-dependent manner. In those with SPPB scores of 8 or 9, the BR group had a higher risk of mobility disability than controls. MR and AR groups had a lower risk of mobility disability than the BR group. CONCLUSIONS: In older adults with PF&S, adherence to PA recommendations is associated with lower incidence of mobility disability. This benefit depends on the degree of adherence as well as baseline physical performance. TRIAL REGISTRATION: ClinicalTrials.gov NCT02582138.
Keywords: Mobility Limitation; Aged, 80 and over; Persons with Disabilities; Sarcopenia; Male; senioři nad 80 let; omezení pohyblivosti; Aged; lidé; Female; mužské pohlaví; ženské pohlaví; senioři; cvičení; sarkopenie; Humans; Exercise; postižení